2019
DOI: 10.1007/s00167-019-05746-2
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of bone graft augmentation to arthroscopic Bankart repair for recurrent anterior shoulder instability with glenoid bone loss

Abstract: Purpose Glenoid bone loss contributes to recurrent instability after arthroscopic Bankart repair alone. With significant glenoid bone loss, better results have been reported after arthroscopic Bankart repair with glenoid arc reconstruction. However, no reports compare augmentation using bone graft with non‐augmentation for glenoid bone loss. The purpose of this study was to assess clinical results of an arthroscopic Bankart repair with or without arthroscopic bone graft augmentation. It was hypothesized that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
4
Order By: Relevance
“…On the Coleman methodology score, one scored poor, 11 43 studies scored fair, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 37 scored good, 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ...…”
Section: Resultsunclassified
See 3 more Smart Citations
“…On the Coleman methodology score, one scored poor, 11 43 studies scored fair, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 37 scored good, 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ...…”
Section: Resultsunclassified
“… 22 140 24 + + Retrospective + + 1,2,3 1 1 61 Iizawa et al. 66 68 31 + + Retrospective + + 1,2,3 1, 3,4 1,2 72 Lavoué et al. 23 41 72 +/− + Retrospective + + 1,2,3 1,3,4 1 67 Pandey et al.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Nakagawa et al 20 reported a complete bone union rate in 50% of patients with small bone fragments (<5% of the glenoid diameter) after arthroscopic bony Bankart repair, while shoulders with medium (5%-10%) and large (>10%) fragments had union rates of 56.3% and 86.7%, respectively. Alternatively, Iizawa et al 12 found that patients treated for bony Bankart lesions (with >20% glenoid bone loss [GBL]) using an iliac crest bone graft or artificial graft had bone union rates of 100% (7/7 patients) and 75% (21/28 patients), respectively. Discrepancies in the current literature therefore necessitate further investigation of bone fragment resorption patterns and optimal surgical intervention for the treatment of bony Bankart lesions.…”
mentioning
confidence: 99%